All-optical switching based on interacting exciton polaritons in self-assembled perovskite microwires - Feng, Jiangang (2022)
Ultrafast all-optical switches and integrated circuits call for giant optical nonlinearity to minimize energy consumption and footprint. Exciton polaritons underpin intrinsic strong nonlinear interactions and high-speed propagation in solids, thus affording an intriguing platform for all-optical devices. However, semiconductors sustaining stable exciton polaritons at room temperature usually exhibit restricted nonlinearity and/or propagation properties. Delocalized and strongly interacting Wannier-Mott excitons in metal halide perovskites highlight their advantages in integrated nonlinear optical devices. Here, we report all-optical switching by using propagating and strongly interacting exciton-polariton fluids in self-assembled CsPbBr3 microwires. Strong polariton-polariton interactions and extended polariton fluids with a propagation length of around 25 μm have been reached. All-optical switching on/off of polariton propagation can be realized in picosecond time scale by locally blue-shifting the dispersion with interacting polaritons. The all-optical switching, together with the scalable self-assembly method, highlights promising applications of solution-processed perovskites toward integrated photonics operating in strong coupling regime.